Prvo opazovanje dolgorepe govnačke Stercorarius longicaudas v Sloveniji - Denac, Damijan (Acrocephalus, 2000)
On July 3rd 1996, a Long-tailed Skua was sighted on the Drava river at Markovci near Ptuj for the very first time in Slovenia. It was watched by fiveornithol-ogists and documented with photographs and video film. The observed individual was an adult in summer plumage. Most of the sightings of Skuas in Slovenia are from reservoirs on the Drava river (5), where Arctic Stercorarius parasiticus, Pomarine S. pomarinus and Long-tailed S. longicaudusSkuas have been recorded. The occurrence of S. longicaudus on Ptuj reservoir is probably related to the cyclone, which had a few days prior to the sighting raged almost over the entire Central Europe and in Slovenia caused prolonged heavy rains accompanied with floods.
Keywords: bird; Birds; ptice; Ecosystem; ornitologija